Fitocenološka združba kot kazalnik občutljivosti gozdnih tal za vožnjo gozdarske mehanizacije - Gašper Ogrin (Slovenian Forestry Institute, 2020)
In the article we determine the suitability of the phytocenose as a basic unit for determining soil susceptibility to mechanized logging. A total of 90 measurements of skid trail profiles were taken on a 13.9 km long sample transect. The forest infrastructure studied was categorized into primary and secondary skid trails, trails intended for CTL harvesting and undocumented trails. The following indicators were determined on the profiles: tyre track depth, trail width, trail slope, amount of rock present, presence of roots and road category. The deepest ruts were found in Blechno-Fagetum (6.9 cm), followed by Galio rotundifolii-Abietetum (6.4 cm) and Hacquetio-Fagetum (5.6 cm), while the shallowest ruts were found in Omphalodo-Fagetum (5.3 cm). The deepest ruts were found on primary skid trails (7.0 cm), followed by secondary skid trails (5.8 cm), while the shallowest ruts were found on skid trails used by CTL technology and on undocumented trails (1.9 cm). No significant difference in track depth was found between the four individual phytosociological units, but more extensive research should be conducted in the future.